The Role of Training and Development in Enhancing Employee Competence to Realize an Innovative and Efficient Organizational Work Environment - Ifan Sadewa; Ridwan Ridwan (Greenation Management and Business Review, 2024)
This study uses a descriptive qualitative research design with a stable model in the teaching process to develop innovative and effective work practices in the workplace. Innovation is the process of improving work according to the needs of employees. Employee training and development have become an important component of today's organizational strategy to achieve competitive advantage. By adopting a dynamic business environment, companies are encouraged to enhance employee competencies to remain relevant and competitive. If employees are encouraged to be creative and innovative, then innovation will come to fruition. It will become necessary when someone decides to engage in non-routine cognitive work. Learning and growth are very important among the many growth resource practices that help employees continuously enhance the knowledge, skills, and abilities necessary for innovation. It is important for organizations to focus on developing innovative behavior among their employees in order to drive innovation. Employees are not always supported by their employers to be innovative and to understand the importance of innovation as well as the need to learn the skills that are prerequisites for innovative work. All of this shows that structured learning programs tailored to the field can enhance students' technical abilities, mastery of soft skills, and work ethic. In addition, the continuation of development has proven to have a positive impact on the overall performance of the organization. This conceptual model explores how non-routine work can be effectively accomplished through innovative work practices.